2022
DOI: 10.3390/plants11040548
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Isoflavones in the Flowers of Pueraria lobata by qHNMR

Abstract: Pueraria lobata (Willd.) Ohwi. is a widely used medicinal plant in Korea, China, and Japan. The flower of P. lobata (Puerariae Flos) contains various bioactive substances such as triterpenoidal saponins and isoflavonoids. In this study, we developed a quantitative analysis of the isoflavones of Puerariae Flos by quantitative proton nuclear magnetic resonance (qHNMR) spectroscopy using the internal calibrant (IC). From the qHNMR results, the isoflavone content was found to be 7.99% and 10.57% for the MeOH sonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Pueraria lobata is an abundant source of isoflavones ( Yao et al, 2021 ). Here, six active isoflavones were examined and identified as puerarin, daidzein, daidzin, genistein, rutin and apigenin in FPE using LC-MS techniques, which is consistent with previous studies ( Liu et al, 2012 ; Thapa et al, 2022 ). Network pharmacology analysis of the active components of Pueraria lobata for the treatment of IBD revealed that the biological activity of Pueraria lobata was also mainly reflected in isoflavones ( Supplementary Table S1 ).…”
Section: Discussionsupporting
confidence: 88%
“…Pueraria lobata is an abundant source of isoflavones ( Yao et al, 2021 ). Here, six active isoflavones were examined and identified as puerarin, daidzein, daidzin, genistein, rutin and apigenin in FPE using LC-MS techniques, which is consistent with previous studies ( Liu et al, 2012 ; Thapa et al, 2022 ). Network pharmacology analysis of the active components of Pueraria lobata for the treatment of IBD revealed that the biological activity of Pueraria lobata was also mainly reflected in isoflavones ( Supplementary Table S1 ).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, the tank is too big to create an ultrasonic blank region, which negatively impacts the effectiveness of the extraction process. Punam [ 46 ] employed several extraction techniques and methanol as the extraction solvent to extract isoflavones from KR flowers. Comparisons were made between the methanol ultrasonic extract (PLs) and the methanol reflux extract (PLr).…”
Section: Sample Pretreatment Methodsmentioning
confidence: 99%
“…Additionally, semi-preparative HPLC is a quick and efficient separation technique for high-purity puerarin isoflavones. Using semi-preparative reverse-phase HPLC, Punam [ 46 ] isolated and purified isoflavones from the flowers of KR. When isoflavones from KR flowers were extracted using various techniques, the concentration ranged from 7.99% to 10.57%.…”
Section: Sample Pretreatment Methodsmentioning
confidence: 99%
“…Its tuber and leaves contain significant phytochemicals and extracts that have historically been used in medicine and nutrition, such as puerarin, daidzein, daidzin, iris, and irisin [ 4 ]; [ 2 ]. These phytochemicals have benefits that include improved immunity, blood lipid control, hypoglycemia, anti-arrhythmia, anti-hepatotoxic, anti-oxidant, anti-mutagenic, anti-myocardial ischemia, and anti-dipsotropic [ 5 ]; [ 6 ]. In studies with alcohol-induced inflammatory conditions, researchers elucidated several plant-derived additives capable of lessening the impact of congeners [ 7 ]; Kudzu showed the best congener-impact lessening results due to its flavonoids contents (amongst other health benefits).…”
Section: Introductionmentioning
confidence: 99%